Determination of low-aliphatic aldehydes indoors by micellar electrokinetic chromatography using sample dissolution manipulation for signal enhancement - Pereira, E. A.; Cardoso, A. A.; Tavares, MFM (Wiley-Blackwell, 2003)
This work describes a novel approach for the analysis of selected aldehydes (formaldehyde, acetaldehyde, propionaldehyde, and acrolein) and acetone in environmental samples using micellar electrokinetic chromatography (MEKC). The method is based on the reaction of carbonyl compounds with 3-methyl-2-benzothiazoline hydrazone (MBTH) that gives an azine intermediate with maximum absorbance at 216 nm. A systematic evaluation of sample dissolution medium was conducted as a means to enhancing sensitivity. In the best condition, samples were dissolved in 0.030 mol.L-1 tetraborate solution. This condition presented enhancement factors in the range of 35-54 for the aldehydes under investigation, computed as the improvement of the concentration limits of detection (LODs) with reference to the sample dissolved in pure water. The running buffer was 0.020 mol.L-1 tetraborate, pH 9.3, containing 0.050 mol-L-1 sodium dodecyly sulfate (SIDS). The overall methodology presented several advantages over established methods for aldehydes. Worthy mentioning that MBTH is available in high purity degree, dispensing laborious reagent purification procedures. A few method validation parameters were determined revealing good migration time repeatability (< 2.5% coefficient of variation, CV) and area repeatability (< 4% CV), excellent linearity (20-120 mug/L, r > 0.995) and adequate sensitivity for environmental applications. The LODs with respect to each single aldehyde were in the range of 0.54-4.0 mug.L-1 and 11 mug.L-1 for acetone. The methodology was applied to the determination of aldehydes indoors. Samples were collected in an impinger flask containing 0.05% MBTH solution, at a flow rate of 0.80 L.min(-1), during 2.5 h, at different times during the day. The most abundant carbonyls in the samples were acetone, followed by formaldehyde and acetaldehyde, with estimate peak concentrations of 452, 5.2 and 2.2 ppbv, respectively.
Keywords: aldehyde; indoors air; micellar electrokinetic chromatography; 3-Methyl-2-benzothiazoline hydrazone